2016
DOI: 10.1371/journal.pone.0151360
|View full text |Cite
|
Sign up to set email alerts
|

Altered Spontaneous Activity in Patients with Persistent Somatoform Pain Disorder Revealed by Regional Homogeneity

Abstract: Persistent somatoform pain disorder (PSPD) is a mental disorder un-associated with any somatic injury and can cause severe somatosensory and emotional impairments in patients. However, so far, the neuro-pathophysiological mechanism of the functional impairments in PSPD is still unclear. The present study assesses the difference in regional spontaneous activity between PSPD and healthy controls (HC) during a resting state, in order to elucidate the neural mechanisms underlying PSPD. Resting-state functional Mag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 70 publications
1
22
0
Order By: Relevance
“…Considering the functional convergence in prefrontal cognitions [53] and its deactivation in psychiatric patients [22,23], it is conceivable that the comprehensive cognitive and metacognitive capacities such as subjective evaluation of somatic sensory cognition might be modulated in OD patients. Furthermore, cortical modifications associated with somatoform states have been suggested in m-PFC function [9][10][11][12][13]. In the present study, we found not only prefrontal deactivation during chewing but also found associated deterioration of somatization scores in OD patients.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Considering the functional convergence in prefrontal cognitions [53] and its deactivation in psychiatric patients [22,23], it is conceivable that the comprehensive cognitive and metacognitive capacities such as subjective evaluation of somatic sensory cognition might be modulated in OD patients. Furthermore, cortical modifications associated with somatoform states have been suggested in m-PFC function [9][10][11][12][13]. In the present study, we found not only prefrontal deactivation during chewing but also found associated deterioration of somatization scores in OD patients.…”
Section: Discussionsupporting
confidence: 72%
“…Neuropsychological evidence for somatization and somatoform disorders has shown cortical associations with the superior medial prefrontal cortex, temporal region, and parietal region [9][10][11][12][13]. For example, Su et al [13] reported a positive relationship between somatization subscale and bilateral superior medial prefrontal activities in patients with somatoform pain disorders.…”
Section: Introductionmentioning
confidence: 99%
“…ReHo abnormalities within regions of the brain reflect alterations in the synchronization of temporal neural activities (Zhong et al, 2011), which suggests that there is unbalanced local functionality or noncompensatory reactions in the whole-brain network (Dai et al, 2012). This approach has been used to identify specific pathophysiological functional signatures and to reveal the neural mechanisms underlying dysfunctions in various brain disorders (Huang et al, 2016;Wang et al, 2014;Wu et al, 2011).…”
mentioning
confidence: 99%
“…For instance, it was found that somatoform pain disorder patients exhibited higher regional homogeneity (ReHo) in the left precentral gyrus, the prefrontal cortex and default-mode network, but decreased ReHo in the bilateral primary somatosensory cortex, the posterior cerebellum, and the occipital lobe comparing with healthy controls. 8,9 Further, using independent component analysis to isolate intrinsic connectivity networks (ICNs) and to calculate the functional network connectivity (FNC) such as intra-and inter-ICNs, Zhao and his colleagues found altered FNCs between the sensorimotor network, the audio network, the visual network, the default-mode network, the executive control network, the salience network, the right-frontoparietal network, the left-frontoparietal network, and the cerebellum network in PSPD patients. 10 A resting-state EEG study revealed that somatoform pain disorder patients exhibited hyperexcitability resting-state cortical oscillations at the parietal region.…”
Section: Introductionmentioning
confidence: 99%